2018
DOI: 10.1016/j.celrep.2018.08.057
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of S100A8 Stability by RNF5 in Intestinal Epithelial Cells Determines Intestinal Inflammation and Severity of Colitis

Abstract: SUMMARYInflammatory bowel disease (IBD) is prevalent, but the mechanisms underlying disease development remain elusive. We identify a role for the E3 ubiquitin ligase RNF5 in IBD. Intestinal epithelial cells (IECs) express a high level of RNF5, while the colon of Rnf5−/− mice exhibits activated dendritic cells and intrinsic inflammation. Rnf5−/− mice exhibit severe acute colitis following dextran sodium sulfate (DSS) treatment. S100A8 is identified as an RNF5 substrate, resulting in S100A8 ubiquitination and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
49
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(50 citation statements)
references
References 31 publications
1
49
0
Order By: Relevance
“…Enhanced DC number and activity were identified in the gut of Rnf5 −/− mice, reflected in (i) increased CD11c + DCs seen in the PP of tumor-bearing Rnf5 −/− mice, (ii) production of more cytokines and chemokines, (iii) greater induction of T cell cytokines by DCs from GALTs of tumor-bearing Rnf5 −/− mice, and (iv) enhanced frequency of CCR7 + DCs and mDCs in GALTs of tumor-bearing Rnf5 −/− mice, which coincides with greater migration properties. In a recent study 36 , we identified a significant increase in the frequency of total colonic DCs in colonic lamina propria cells from naive Rnf5 −/− mice compared with the WT genotype. Notwithstanding, our findings are in line with previous reports implicating altered UPR signaling in enhanced innate immunity associated with colitis and related inflammatory disorders 37,38 .…”
Section: Discussionmentioning
confidence: 79%
See 2 more Smart Citations
“…Enhanced DC number and activity were identified in the gut of Rnf5 −/− mice, reflected in (i) increased CD11c + DCs seen in the PP of tumor-bearing Rnf5 −/− mice, (ii) production of more cytokines and chemokines, (iii) greater induction of T cell cytokines by DCs from GALTs of tumor-bearing Rnf5 −/− mice, and (iv) enhanced frequency of CCR7 + DCs and mDCs in GALTs of tumor-bearing Rnf5 −/− mice, which coincides with greater migration properties. In a recent study 36 , we identified a significant increase in the frequency of total colonic DCs in colonic lamina propria cells from naive Rnf5 −/− mice compared with the WT genotype. Notwithstanding, our findings are in line with previous reports implicating altered UPR signaling in enhanced innate immunity associated with colitis and related inflammatory disorders 37,38 .…”
Section: Discussionmentioning
confidence: 79%
“…Noteworthy, Rnf5 −/− mice exhibit basal intestinal inflammation, which develops into acute colitis following DSS administration 36 . S100A8, which was identified as a RNF5 substrate capable of mediating the acute colitis phenotype, and administration of neutralizing S100A8 antibodies blocked the colitis phenotypes 36 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Immunohistochemical (IHC) staining was performed as previously described with minor modification on the paraffin‐embedded lung tissues 12 . Staining intensity of LAMP2A (# ab125068; Abcam) was scored using a four‐tier scale from 0 (no staining) to 3 (strongest staining).…”
Section: Methodsmentioning
confidence: 99%
“…S100A8 has emerged as an inflammatory factor and is associated with cancer. S100A8 is increasingly recognized as a biomarker in many solid tumors, such as head and neck squamous cell carcinoma ( 6 ), as well as colon ( 7 ), ovarian ( 8 ), bladder, and breast cancers ( 9 ). Recently, studies have shown that S100A8 is a potential indicator of poor survival in acute myeloid leukemia (AML) ( 10 ), and increased mRNA levels of S100A8 were associated with progression in breast cancer ( 11 ).…”
Section: Introductionmentioning
confidence: 99%